Platonic Golden Network Theory for High Energy Physics and Quantum Cosmology (Global Journal of Science Frontier Research, 2020)
In the spirit of Pythagorean cosmic mathematical music of numbers and following the fundamental tenets of platonic transfinite set theory and the methodology of E-infinity Cantorian spacetime, we present a golden section based network with deep physical meaning confirming experimental results in high energy physics as well as cosmological measurements and observations related to the phenomenon of cosmic dark energy and dark matter.
Keywords: E-infinity; cantorian spacetime; fractal spacetime